2022
DOI: 10.1155/2022/6780575
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and Clinical Characteristics of Hospitalized Pediatric Patients with SARS-CoV-2 Infection in Mexico City, Mexico

Abstract: Background. Evidence from across the world suggests that the pediatric population shows different clinical manifestations and has a lower risk of severe presentation of SARS-CoV-2 infection compared to adults. However, Mexico has one of the highest mortality rates in the pediatric population due to SARS-CoV-2 infection. Therefore, our objective was to explore the epidemiological and clinical characteristics associated with a positive confirmatory test in the Mexican pediatric population admitted to a tertiary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
0
1
Order By: Relevance
“…Children and adolescents who died of COVID-19 in the HIMFG were identified between May and December 2020 (first and second waves). Nevertheless, in the first wave of the pandemic, the mortality rate in this population was lower than that in other studies from a different tertiary hospital in Mexico [ 27 ]. In addition, other studies from Brazil and Indonesia have reported higher mortality rates, with 15% and 40%, respectively [ 28 , 29 ].…”
Section: Discussioncontrasting
confidence: 61%
“…Children and adolescents who died of COVID-19 in the HIMFG were identified between May and December 2020 (first and second waves). Nevertheless, in the first wave of the pandemic, the mortality rate in this population was lower than that in other studies from a different tertiary hospital in Mexico [ 27 ]. In addition, other studies from Brazil and Indonesia have reported higher mortality rates, with 15% and 40%, respectively [ 28 , 29 ].…”
Section: Discussioncontrasting
confidence: 61%